Extend Nearly Pseudo Quasi-2-Absorbing Submodules (II) - Omar A. Abdullah; Karim Mohammadali, Haibat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The concept of the Extend Nearly Pseudo Quasi-2-Absorbing submodules was recently introduced by Omar A. Abdullah and Haibat K. Mohammadali in 2022, where he studies this concept and it is relationship to previous generalizationsm especially 2-Absorbing submodule and Quasi-2-Absorbing submodule, in addition to studying the most important Propositions, charactarizations and Examples. Now in this research, which is considered a continuation of the definition that was presented earlier, which is the Extend Nearly Pseudo Quasi-2-Absorbing submodules, we have completed the study of this concept in multiplication modules. And the relationship between the Extend Nearly Pseudo Quasi-2-Absorbing submodule and Extend Nearly Pseudo Quasi-2-Absorbing ideal. We also studied more result of Extend Nearly Pseudo Quasi-2-Absorbing submodule in multiplication module. In the end, we obtained new Propositions and distinguished results in studying this concept.